Advances in HIV Treatment and Vaccine Development: Emerging Therapies and Breakthrough Strategies for Long-Term Control - Olalekan John Okesanya; Racheal Ahuoyiza Ayeni; Promise Amadin; Ifeanyi Ngwoke; Blessing Olawunmi Amisu; Bonaventure Michael Ukoaka; Mohamed Mustaf Ahmed; Tolutope Adebimpe Oso; Shuaibu Saidu Musa; Don Eliseo Lucero-Prisno (AIDS Research and Treatment)
Trial Registration: ClinicalTrials.gov identifier: NCT02120352, NCT02938520, NCT03639311, NCT03497676, NCT03635788